CONVERGENT CONCEPT OF BRANDING FOR CORPORATE BEHAVIORAL PROJECTING - Vladimir M. Kiselev; Oksana V. Korkacheva; Sergey V. Savinkov; Andrey V. Ivanov; Anna V. Fedorova (Вестник Российского экономического университета имени Г. В. Плеханова)
Socially important projects aiming at customer behaviour and solutions influence lately both society and work of separate companies, governmental institutions and the whole state. The article provides the concept of convergent customer-behaviour, where special attention is paid to convergence of sciences not very closely connected with each other, for example economics and physiology, marketing and project management, sociology and psychology, behaviorism and conflictology, inter-person communication and innovating. At the same time the authors write that theory and methodology of these sciences are complementary in respect to the most important aspects of human activity affecting the quality of society life in general or its part. The focus of assessing the results of projecting technical (technological) or social innovations should be moved to humanization of the goals and socialization of problems resolved. Convergence of scientific tools designed by the authors for such projecting evolve the concept of projecting into socio-technical model.